Method for forming coated floor

A coating material with single-walled carbon nanotubes, a wet dispersant, and additives ensures high conductivity at 50V, addressing the conductivity and finishing issues of conventional coatings, preventing static electricity damage and maintaining a smooth finish.

JP2025020433APending Publication Date: 2025-02-12SUMITOMO RUBBER INDUSTRIES LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024200039
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-12

AI Technical Summary

Technical Problem

Conventional coating materials using curable resins for floors do not exhibit electrical conductivity at low voltages such as 50V, leading to static electricity damage, and adding large amounts of conductive fillers like carbon nanotubes results in increased viscosity and poor finishing properties.

Method used

A coating material comprising a room temperature curable resin, single-walled carbon nanotubes, a wet dispersant with acidic and amino groups, a leveling agent, and an anti-foaming agent, which allows for high conductivity at 50V while maintaining excellent finishing properties.

Benefits of technology

The coating material achieves high conductivity at 50V with a cured coating film resistance of less than 10^9 Ω, preventing static electricity damage and ensuring a smooth, bubble-free finish.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025020433000001
    Figure 2025020433000001
  • Figure 2025020433000002
    Figure 2025020433000002
Patent Text Reader

Abstract

To realize a coated floor material using carbon nano-tube, excellent in finish property, and showing high conductivity in a cured coated film of 50 V.SOLUTION: A method for forming a coated floor of a single layer structure, including a step of forming a layer of a cured coated film of a coated floor material by coating the coated floor material on a floor to be constructed is such that: the coated floor material contains a normal temperature-curable type resin, single layer carbon nano-tube, a wet dispersant, a leveling agent and an antifoaming agent; and the wet dispersant is polymer salt including an acidic group and an amino group. Alternatively, a method for forming a coated floor of a multilayer structure includes: a step of forming a primer layer on a floor to be constructed; and a step of coating a coated floor material on the primer layer to form a layer of a cured coated film of the coated floor material, and therein, the coated floor material contains a normal temperature-curable type resin, single layer carbon nano-tube, a wet dispersant, a leveling agent and an antifoaming agent, and the wet dispersant is polymer salt including an acidic group and an amino group.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a coated floor material having improved antistatic performance. The present invention also relates to a coated floor including a cured coating film of the coated floor material. [Background technology]

[0002] Coating floors using curing resins such as epoxy resins are often used for floors in production facilities such as factories. However, since the curing resins used in coating floors are electrically insulating, problems occur in that static electricity occurs during work on the coated floors. Therefore, in order to impart antistatic properties to the coated floors, conductive fillers are added to the curing resins. For example, Patent Document 1 describes the use of conductive titanium oxide powder and carbon fibers as conductive fillers. Patent Document 2 describes the use of carbon fibers as conductive fillers. Patent Document 3 describes the use of conductive metal oxides such as conductive zinc oxide and stainless steel fibers as conductive fillers.

[0003] The leakage resistance when static electricity charged to the human body is grounded through a painted floor is 10 8 It is said that a resistance of about 10 Ω is sufficient. Therefore, an antistatic coating floor should have a resistance of 10 Ω or less when measured with an applied voltage of 500 V. 8 It has a conductivity of less than Ω. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2013-40446 A [Patent Document 2] JP 2017-48333 A [Patent Document 3] JP 2016-223252 A Summary of the Invention [Problem to be solved by the invention]

[0005] On the other hand, in production facilities, electrostatic damage such as the destruction of electronic components at low voltages may occur. In contrast, conventional coated floors have a sea-island structure with a curable resin as the sea phase and a conductive filler as the island phase. In a sea-island structure, electricity flows between the island phases on either side of the sea phase, so a certain voltage or higher is required for electrical conductivity. For this reason, conventional coated floors do not exhibit electrical conductivity at low voltages such as 50V, and cannot prevent electrostatic damage at such low voltages. Therefore, there is a demand for the development of coated floors that exhibit electrical conductivity even at low voltages such as 50V.

[0006] Here, in order to improve the electrical conductivity, it is considered to add a large amount of conductive filler to the conventional coating floor material. However, adding a large amount of conductive filler leads to an increase in the viscosity of the coating floor material, which results in a decrease in the coating workability and a poor finish of the coating floor. Specifically, sufficient flatness and gloss cannot be obtained, and this leads to the occurrence of coating film defects such as air bubbles.

[0007] On the other hand, carbon nanotubes are known as a material with high electrical conductivity. However, carbon nanotubes cause an increase in viscosity due to aggregation, which also leads to poor finish of the coated floor. For this reason, a coated floor material using carbon nanotubes with excellent finish has not been realized.

[0008] In view of the above circumstances, an object of the present invention is to provide a coated floor material using carbon nanotubes that has excellent finish and exhibits high electrical conductivity even at 50V when the cured coating film is applied. [Means for solving the problem]

[0009] The present invention relates to a floor coating material comprising a room temperature curing resin, single-walled carbon nanotubes, a wetting and dispersing agent, a leveling agent, and an antifoaming agent, wherein the wetting and dispersing agent is a polymer salt containing an acidic group and an amino group. Effect of the Invention

[0010] According to the present invention, it is possible to provide a coated floor material using carbon nanotubes which has excellent finish and exhibits high electrical conductivity even at 50V when the cured coating film is applied. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The floor coating material of the present invention contains a room temperature curing resin, single-walled carbon nanotubes, a wetting and dispersing agent, a leveling agent, and a defoaming agent. The wetting and dispersing agent is a polymer salt containing an acid group and an amino group.

[0012] [Room temperature curing resin] The room temperature curing resin is a resin that can be cured at room temperature (for example, 0°C to 40°C, particularly 5°C to 35°C), which is the construction environment temperature, and known resins for floor coating applications can be used. As the room temperature curing resin, two-component curing type, moisture curing type, radical polymerization type, etc. can be used, and among these, two-component curing type is preferable. Specific examples of the room temperature curing resin include epoxy resin, urethane resin, acrylic resin, polyester resin, vinyl ester resin, etc., and among these, epoxy resin is preferable.

[0013] As the epoxy resin, any epoxy resin known in the art for use in floor coating materials can be used, and two-component curing type epoxy resins that are liquid at room temperature and cure by reaction with a curing agent are preferred.

[0014] Examples of epoxy resins include alicyclic epoxy resins such as 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate; glycidyl ester type epoxy resins such as hexahydrophthalic acid diglycidyl ester; bisphenol type epoxy resins derived from bisphenols such as bisphenol A and bisphenol F and epihalohydrins; epoxidized novolac resins such as phenol novolac resin, cresol novolac resin, bisphenol A novolac resin, naphthol novolac resin, and biphenyl novolac resin; glycidyl ether type epoxy resins derived from dihydric alcohols such as hydrogenated bisphenol F, hydrogenated bisphenol A, 1,4-cyclohexanedimethanol, and alkylene oxide adducts of bisphenol A and epihalohydrins; and epoxy resins derived from polyhydric phenols such as hydroquinone and catechol and epihalohydrins. Among these, bisphenol type epoxy resins (particularly, bisphenol A type epoxy resins) are preferred. These can be used alone or in combination of two or more.

[0015] As the curing agent, those known in the application of floor coating materials can be used. Specific examples thereof include aliphatic amines such as diethylenetriamine, triethylenetetramine, pentaethylenehexamine, etc., or modified products thereof; aromatic amines such as m-phenylenediamine, m-xylylenediamine, diaminodiphenylmethane, etc., or modified products thereof; alicyclic amines such as 1,3-bis(aminomethyl)cyclohexane, isophoronediamine, etc., or modified products thereof; acid anhydrides such as phthalic anhydride, hexahydrophthalic anhydride, pyromellitic anhydride, etc.; polysulfides; acid amides; thiokol, etc. Among them, alicyclic amines, aromatic amines, and modified products thereof are preferred. Modified products include Mannich modified products, adduct modified products, etc. These can be used alone or in combination of two or more.

[0016] The mixing amount of epoxy resin and curing agent may be set so that the molar amount of epoxy groups contained in the epoxy resin and the molar amount of active hydrogen contained in the curing agent are approximately equal, as in the conventional method. When a reactive diluent is used, which will be described later, the total molar amount of epoxy groups contained in the epoxy resin and the reactive diluent may be set so that the molar amount of active hydrogen contained in the curing agent is approximately equal.

[0017] [Single-walled carbon nanotubes] In the present invention, single-walled carbon nanotubes (SWNTs) are used as the conductive filler. SWNTs have a structure in which one graphene sheet is rolled into a cylindrical shape. The single-walled carbon nanotubes may be of any of the armchair type, zigzag type, and chiral type. Since they can be easily dispersed in the floor coating material, it is preferable to use pre-dispersed single-walled carbon nanotubes, and in particular, it is preferable to use those pre-dispersed in a diluent that is reactive with room temperature curing resins. Single-walled carbon nanotubes can be synthesized according to a known method and are also available as commercial products. A suitable example of pre-dispersed single-walled carbon nanotubes is "TUBALL MATRIX201" manufactured by OCSIAL. This "TUBALL MATRIX201" contains fatty acid glycidyl ester as a reactive diluent. Therefore, when an epoxy resin is used as the room temperature curing resin, the fatty acid glycidyl ester can react with the curing agent together with the epoxy resin.

[0018] The content of single-walled carbon nanotubes in the coating floor material is not particularly limited, but if it is too small, the conductivity may be insufficient. Therefore, the content of single-walled carbon nanotubes in the coating floor material (i.e., relative to the total mass of the coating floor material; in the case of a two-component type room temperature curing resin, relative to the total mass of the coating floor material including the mass of the curing agent) is preferably 0.010% by mass or more, more preferably 0.015% by mass or more, and even more preferably 0.020% by mass or more. On the other hand, if the content of single-walled carbon nanotubes in the coating floor material is too high, the coating floor material may thicken and the finish may be impaired. Therefore, the content of single-walled carbon nanotubes in the coating floor material is preferably 0.040% by mass or less, more preferably 0.035% by mass or less, and even more preferably 0.030% by mass or less.

[0019] [Wetting and dispersing agent] In the present invention, a wetting dispersant is used. In the field of paints, the wetting dispersant is an additive that functions as a surfactant to improve the wettability of the coating film, and as a dispersant that prevents particle aggregation by mechanisms such as electrical repulsion and steric hindrance. Among the wetting dispersants, a wetting dispersant that is a polymer salt containing an acidic group and an amino group is used in the present invention. By using such a wetting dispersant, even when single-walled carbon nanotubes are used, it is possible to prevent the aggregation of single-walled carbon nanotubes in the floor coating material, and to suppress the deterioration of the finish due to thickening.

[0020] The acidic group is preferably an acidic phosphate group. The polymer of the polymer salt may be a homopolymer or a copolymer. The polymer is preferably a graft copolymer in which one or more side chains (e.g., polyester chains) are introduced into a main chain (e.g., polyurethane chain). In this case, the dispersibility of the single-walled carbon nanotubes is improved due to the steric hindrance of the polymer chain. As the polymer salt, alkyl ammonium salts and phosphate salts are preferred, and alkyl ammonium salts are more preferred.

[0021] The wetting dispersant preferably has an acid value and an amine value of 10 mgKOH / g or more. From the viewpoint of storage stability, the acid value and the amine value of the wetting dispersant are more preferably 30 mgKOH / g or more, and even more preferably 35 mgKOH / g or more. The acid value refers to the acid value per 1 g of polymer dispersant solid content, and can be determined, for example, by potentiometric titration in accordance with JIS K0070. The amine value refers to the amine value per 1 g of polymer dispersant solid content, and can be determined, for example, by using a 0.1 N hydrochloric acid aqueous solution and converting the value determined by potentiometric titration into the equivalent amount of potassium hydroxide.

[0022] Examples of wetting and dispersing agents that can be used in the present invention include "BYK-9076" and "DISPERBYK-142" manufactured by BYK Japan Co., Ltd. and "Disparlon DA-325" manufactured by Kusumoto Chemical Industries, Ltd., with "BYK-9076" and "DISPERBYK-142" being preferred. Wetting and dispersing agents can be used alone or in combination of two or more.

[0023] The content of the wetting dispersant in the coating floor material is not particularly limited, but if it is too small, sufficient conductivity may not be obtained. In addition, the higher the content of the wetting dispersant, the higher the storage stability tends to be. Therefore, the content of the wetting dispersant in the coating floor material is preferably 0.04 mass% or more, more preferably 0.10 mass% or more, and even more preferably 0.15 mass% or more. On the other hand, if the content of the wetting dispersant in the coating floor material is too high, the conductivity may decrease. Therefore, the content of the wetting dispersant in the coating floor material is preferably 0.40 mass% or less, more preferably 0.32 mass% or less, and even more preferably 0.25 mass% or less.

[0024] [Leveling Agent] In the present invention, a leveling agent is used. The use of the leveling agent can improve the finish. The leveling agent may be a known one used in floor coating materials. Examples of the leveling agent include acrylic polymers. The leveling agent may be the "Polyflow" series manufactured by Kyoeisha Chemical Co., Ltd. The leveling agent may be used alone or in combination of two or more types.

[0025] The content of the leveling agent in the coating floor material is not particularly limited, but if it is too small, the finish may be deteriorated. Therefore, the content of the leveling agent in the coating floor material is preferably 0.04 mass% or more, more preferably 0.06 mass% or more, and even more preferably 0.07 mass% or more. On the other hand, if the content of the leveling agent in the coating floor material is too high, the conductivity may be insufficient. Therefore, the content of the leveling agent in the coating floor material is preferably 0.21 mass% or less, more preferably 0.18 mass% or less, and even more preferably 0.15 mass% or less.

[0026] [Antifoaming agent] In the present invention, a defoaming agent is used. The use of a defoaming agent can improve the finish. The defoaming agent may be a known agent used in floor coating materials. Examples of the defoaming agent include acrylic polymers, vinyl ether polymers, and mixtures thereof. The defoaming agent may be the "Florene" series manufactured by Kyoeisha Chemical Co., Ltd. The defoaming agent may be used alone or in combination of two or more types.

[0027] The content of the defoaming agent in the coating floor material is not particularly limited, but if it is too small, the finish may be deteriorated. Therefore, the content of the defoaming agent in the coating floor material is preferably 0.12 mass% or more, more preferably 0.18 mass% or more, and even more preferably 0.24 mass% or more. On the other hand, if the content of the defoaming agent in the coating floor material is too high, the conductivity may be insufficient. Therefore, the content of the defoaming agent in the coating floor material is preferably 0.40 mass% or less, more preferably 0.38 mass% or less, and even more preferably 0.36 mass% or less.

[0028] The floor coating material of the present invention may contain a pigment for the purpose of adjusting the color tone. As the pigment, a known pigment used in floor coating materials may be used. The content of the pigment may be appropriately set according to the type of pigment and the desired color tone.

[0029] The coated floor material of the present invention may contain an insulating filler for the purpose of improving strength, colorability, etc. As the insulating filler, a known one used in coated floor materials may be used. Examples thereof include calcium carbonate, magnesium carbonate, barium sulfate, calcium oxide, magnesium oxide, alumina, silica, kaolin, talc, mica, glass beads, glass microballoons, glass fiber, etc., and among them, calcium carbonate (particularly heavy calcium carbonate) is preferable. The content of the insulating filler may be appropriately set according to the desired strength, etc.

[0030] The floor coating material of the present invention may contain a reactive diluent, a non-reactive diluent, etc., for the purpose of viscosity adjustment, etc. Examples of reactive diluents include compounds having one or more reactive groups of the same type as the room temperature curing resin. Specifically, for example, when the room temperature curing resin is an epoxy resin, a compound having an epoxy group such as neopentyl glycol diglycidyl ether can be used. Examples of non-reactive diluents include compounds that do not have the same type of reactive group as the room temperature curing resin. Specifically, for example, when the room temperature curing resin is an epoxy resin, benzyl alcohol, etc. can be used. The content of these may be appropriately set according to the desired viscosity, etc.

[0031] The coated floor material of the present invention may further contain components other than those described above, provided that the effects of the present invention are not significantly impaired.

[0032] The method of preparing the floor coating material of the present invention is not particularly limited, and it can be prepared according to a known method. For example, each component of the floor coating material of the present invention may be mixed at once at the construction site or the like to prepare it. For example, the floor coating material of the present invention may be prepared as a two-liquid type divided into a main agent containing components other than the hardener and a hardener, and the main agent and hardener are mixed and used at the construction site or the like. For example, it may be prepared as a two-liquid type, and the main agent component may be prepared without mixing an insulating filler or with a small amount of insulating filler, and the insulating filler may be added to the main agent so that the mixing amount is determined in consideration of the condition of the base and the characteristics required for the floor coating, for example, at the construction site or the like. For example, it may be prepared as a two-liquid type, and the main agent component may be prepared without mixing a colorant, and the colorant may be added to the main agent according to the color tone required for the floor coating, for example, at the construction site or the like.

[0033] The coated floor material of the present invention can be applied and used according to a known method. For example, the coated floor material of the present invention can be applied to the floor to be applied by a pouring method, and then left to stand for a predetermined time to dry and harden the epoxy resin, thereby forming a coated floor. The applied coated floor may be a single layer of the layer formed by the coated floor material of the present invention (i.e., the layer of the cured coating film of the coated floor material of the present invention), or may be a multi-layer structure combining the layer formed by the coated floor material of the present invention and a primer layer.

[0034] According to the coated floor material of the present invention, by using a wetting dispersant and further combining it with a leveling agent and an antifoaming agent, it is possible to obtain a coated floor that has sufficient flatness and gloss even while using carbon nanotubes. Furthermore, in the coated floor material of the present invention, the occurrence of coating film defects such as air bubbles is suppressed. Therefore, the coated floor material of the present invention has excellent finish. Furthermore, according to the coated floor material of the present invention, the cured coating film exhibits high conductivity even at 50 V. Specifically, the resistance at 50 V is 10 9 Ω or even less than 10 7 Ω or less, especially 10 6It is also possible to achieve a conductivity of Ω or less. Furthermore, the cured coating film can exhibit high conductivity even at 25 V. Therefore, the coated floor material of the present invention has much higher antistatic performance than conventional ones (hence it can be called a "highly antistatic coated floor material"), and can prevent not only conventional antistatic properties, but also electrostatic damage such as destruction of electronic components at low voltages.

[0035] Therefore, from another point of view, the present invention is a coated floor having a cured coating film of the above-mentioned coated floor material. The coated floor may have a primer layer. The thickness of the cured coating film of the above-mentioned coated floor material is not particularly limited, but is, for example, 1.0 mm or more and 3.0 mm or less, preferably 1.0 mm or more and 2.0 mm or less. The coated floor of the present invention has a good finish and shows high conductivity even at 50 V. Therefore, electrostatic damage such as destruction of electronic parts at low voltage is prevented. The coated floor of the present invention can be used in various buildings, and is particularly suitable for research facilities and production facilities of electronic parts. EXAMPLES

[0036] Examples of the present invention will be described below, but it is not intended that the present invention be limited to those shown in these examples.

[0037] [Examples and Comparative Examples] The components shown in Tables 1 and 2 were mixed to prepare a two-liquid coating floor material consisting of a base agent and a hardener. The values ​​in the tables indicate parts by mass. The total amount of the base agent and hardener was about 120 parts by mass.

[0038] [Conductivity evaluation] Primer layer and conductive primer layer (resistance: approx. 10 3A floor coating material of each Example and Comparative Example was applied to a flat plate having a surface roughness of 1000 Ω, and the epoxy resin was cured to prepare a test sample. The resistance of this test sample was measured using an insulation resistance meter when voltages of 500V, 100V, 50V, and 25V were applied in accordance with NFPA and JIS A1454:2016. Iron cylinders weighing 2.25 kg were used as electrodes, and the distance between the electrodes was 3 feet (approximately 91 cm). The measurement results are shown in Tables 1 and 2.

[0039] [Evaluation of Finished State] The floor coating materials of each Example and Comparative Example were applied to a thickness of 1.0 mm on a flat plate with a primer layer formed thereon, and the epoxy resin was cured to prepare a test sample. The surface of the test sample was exposed to fluorescent light to check for uneven reflection. The presence or absence of air bubbles and air bubble marks was also checked. Evaluation was based on the following criteria, and a score of 0 or higher was deemed to be acceptable. The results are shown in Table 1. ⊚: Almost no uneven reflection, and no air bubbles or air bubble marks are observed. ◯: Slight unevenness in reflection is observed, but no air bubbles or air bubble marks are observed. △: Uneven reflection is observed, and slight air bubbles and air bubble marks are also observed. ×: Reflection unevenness is noticeable, and many air bubbles and air bubble marks are observed.

[0040] [Storage Stability Evaluation] After preparing the floor coating materials of each Example and Comparative Example, they were left at room temperature for one month. Using these, the resistance was measured in the same manner as above with an applied voltage of 50 V, and evaluated according to the following criteria. The results are shown in Tables 1 and 2. 〇: Resistance value is 10 6 Less than Ω △: Resistance value is 10 6 Ω or more 10 8 Less than Ω ×: Resistance value is 10 8 Ω or more

[0041] [Table 1]

[0042] [Table 2]

[0043] Polyflow #85: Kyoeisha Chemical Co., Ltd.'s leveling agent "Polyflow #85" FLORON AC324: Defoamer "FLORON AC324" manufactured by Kyoeisha Chemical Co., Ltd. MATRIX201: OCSIAL's "TUBALL MATRIX201" (contains single-walled carbon nanotubes: fatty acid glycidyl ester (reactive diluent) in a mass ratio of 1:9) BYK-9076: Wetting and dispersing agent "BYK-9076" manufactured by BYK Japan (alkyl ammonium salt of a polymer in which a polyester chain is grafted onto a polyurethane main chain; acid value = 38 mg KOH / g, amine value = 44 mg KOH / g) DISPERBYK-142: Wetting and dispersing agent "DISPERBYK-142" manufactured by BYK Japan (phosphate ester salt of high molecular weight copolymer with pigment affinity group; acid value = 46 mg KOH / g, amine value = 43 mg KOH / g) DA-325: Wetting and dispersing agent "Disparlon DA-325" manufactured by Kusumoto Chemicals Co., Ltd. (mixture of polyether phosphate ester and polyamine; acid value = 14 mg KOH / g, amine value = 20 mg KOH / g) BYK-9077: Wetting and dispersing agent "BYK-9077" manufactured by BYK Japan (high molecular weight copolymer with pigment affinity groups; amine value = 44 mg KOH / g) DISPERBYK-2152: Wetting and dispersing agent "DISPERBYK-2152" (hyperbranched polyester) manufactured by BYK Japan

[0044] From the above results, it can be seen that when the floor coating material contains a room temperature curing resin, single-walled carbon nanotubes, a wetting and dispersing agent, a leveling agent, and an antifoaming agent, and the wetting and dispersing agent is a polymer salt containing an acidic group and an amino group, the electrical conductivity is high and a good finish can be obtained even at a low voltage of 50 V. Therefore, it can be seen that the floor coating material of the present invention has excellent finish even though it uses carbon nanotubes, and the cured coating film shows high electrical conductivity even at 50 V.

Claims

1. A method for forming a single-layer coated floor, comprising the steps of applying a coating material to a floor to be constructed and forming a layer of a hardened coating film of the coating material, The floor coating material contains a room temperature curing resin, single-walled carbon nanotubes, a wetting and dispersing agent, a leveling agent, and a defoaming agent, The wetting and dispersing agent is a polymer salt containing an acid group and an amino group. How to form a painted floor.

2. forming a primer layer on the floor to be installed; A method for forming a multi-layered coated floor, comprising the steps of: applying a coating floor material on the primer layer to form a layer of a cured coating film of the coating floor material; The floor coating material contains a room temperature curing resin, single-walled carbon nanotubes, a wetting and dispersing agent, a leveling agent, and a defoaming agent, The wetting and dispersing agent is a polymer salt containing an acid group and an amino group. How to form a painted floor.

3. The method for forming a coated floor according to claim 1 or 2, wherein the content of the single-walled carbon nanotubes is 0.010% by mass or more and 0.040% by mass or less.

4. The method for forming a coated floor according to any one of claims 1 to 3, wherein the content of the wetting dispersant is 0.04% by mass or more and 0.40% by mass or less.

5. The method for forming a coated floor according to any one of claims 1 to 4, wherein the wetting and dispersing agent is an alkyl ammonium salt or a phosphate ester salt.

6. The method for forming a coated floor according to any one of claims 1 to 5, wherein the acid value and amine value of the wetting and dispersing agent are each 30 mg KOH / g or more.

7. The method for forming a coated floor according to any one of claims 1 to 6, wherein the content of the leveling agent is 0.04% by mass or more and 0.20% by mass or less.

8. The method for forming a coated floor according to any one of claims 1 to 7, wherein the content of the defoaming agent is 0.12% by mass or more and 0.40% by mass or less.

9. The method for forming a coated floor according to any one of claims 1 to 8, wherein the thickness of the cured coating film is 1.0 mm or more and 3.0 mm or less.

Citation Information

Patent Citations

  • Novel antistatic terrace system and production method

    CN107652845A

  • Terrace material and preparation method and application thereof

    CN111334174A

  • Solvent-free anti-static matte epoxy terrace compound

    CN111363448A

  • Image recorder

    JP1994102761A

  • Conductive coating-floor paint, conductive coated floor, and building

    JP2014196460A